2011
DOI: 10.1001/archinternmed.2011.502
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Structured Behavioral Intervention on Poorly Controlled Diabetes

Abstract: Background Although maintaining near normal glycemia delays onset and slows progression of diabetes complications, many diabetes patients and their physicians struggle to achieve glycemic targets. Best methods to support patients as they follow diabetes prescriptions and recommendations are unclear. Methods To test the efficacy of a behavioral diabetes intervention in improving glycemia in long-duration, poorly-controlled diabetes, we randomized 222 adults with diabetes (49% type 1, 53±12 years old, 18±12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(174 citation statements)
references
References 41 publications
2
161
0
9
Order By: Relevance
“…The curriculum must be dynamic (5,97,(111)(112)(113). Recent education research endorses the inclusion of practical problem-solving approaches and collaborative care, addressing psychosocial issues, behavior change, and strategies to sustain self-management efforts (40, [114][115][116][117][118][119][120].…”
Section: Standard 5 Dsmes Teammentioning
confidence: 99%
See 1 more Smart Citation
“…The curriculum must be dynamic (5,97,(111)(112)(113). Recent education research endorses the inclusion of practical problem-solving approaches and collaborative care, addressing psychosocial issues, behavior change, and strategies to sustain self-management efforts (40, [114][115][116][117][118][119][120].…”
Section: Standard 5 Dsmes Teammentioning
confidence: 99%
“…Evidence-based communication strategies such as collaborative goal setting, action planning, motivational interviewing, shared decision making, cognitive behavioral therapy, problem solving, selfefficacy enhancement, teach-back, and relapse-prevention strategies are also effective (120,(136)(137)(138)(139). It is crucial to develop action-oriented behavior change goals and objectives (130,140).…”
Section: Standard 7 Individualizationmentioning
confidence: 99%
“…Ritholz et al (80) found that people with diabetes are less likely to discuss self-care information because of a fear of being judged and feeling shame. A randomized controlled trial (n 5 222) demonstrated a mean 1-point A1C lowering when people with type 2 diabetes were taught how to reframe self-blame using more neutral, fact-based messages (84).…”
Section: Use Language That Fosters Collaboration Between Patients Andmentioning
confidence: 99%
“…Despite the widespread support for CGS as a strategy for providing diabetes self-management support in primary care, evidence has focused largely on its use as part of group medical visits [16], comprehensive diabetes self-management classes [17], or counseling provided by certified diabetes educators [18]. Only one randomized controlled trial, using the LWD intervention, has examined implementation and effectiveness of CGS in individual, primary care sessions [19].…”
mentioning
confidence: 99%